Challenges facing Primary School Head Teachers preparedness in Management of Free Primary Education in Siaya County, Kenya - Haruni, Hellen; Odera, Florence Y. (IJRDO- Journal of Educational Research, 2016)
The aim of free primary education (FPE) was to provide more school opportunities for allchildren. In pursuit of this policy objective, the government of Kenya introduced FPE in January2003, resulting to increased enrolment from 5.9 million in 2002 to 7.2 million in 2004. This ledto extra administrative duties for head teachers and continued administrative challenges inmanagement of FPE programme related to lack of clear policy framework, management skills,interpretation of government policies. The purpose of this study was to identify challengesfacing primary school headteachers in management of FPE, with the following specificobjectives; to establish head teachers preparedness in management of FPE in Siaya sub-county,to identify training required by head teachers to manage FPE and to assess stake holdersparticipation in management of FPE in Siaya sub-county. The study employed descriptivesurvey design. Population consisted of 130 public primary school head teachers, one sub countyauditor and one sub quantity assurance and standard officer (SCQASO). Stratified samplingtechnique was used to obtain a sample of 43 public primary schools. Questionnaire, in-depthinterview and observation schedule was used for data collection. Quantitative data was analyzedby use of descriptive statistics, frequencies, percentages, pie charts and graph, while contactanalysis was used to analyze qualitative data. The findings established that head teachers werenot adequately prepared to manage FPE, headteachers also needed to be equipped withmanagement skills to effectively manage FPE. Lastly, stakeholders did not fully supportmanagement of FPE. Based on the findings, it was recommended that head teachers shouldextensively be trained in management of FPE, Quality assurance and standards officers andauditors should be financially empowered to train head teachers on management of FPE andstakeholders should be trained in their role in management of FPE.